Self-Compassion and Self-Control Amongst Recovering Addicts - Brindha Vijayakone; Haslee Sharil Lim Abdullah (Universiti Sains Islam Malaysia, 2024)
This study was aimed to measure Self-compassion and Self-control levels, compare their mean scores based on age, race, marital status, educational level and duration involved in drugs and examine the relationship between Self-compassion and Self-control amongst recovering addicts. This study involved 190 respondents randomly selected from a Cure and Care Rehabilitation Centre (CCRC) located in the state of Johor. Instruments used were the Self-compassion Scale and Self-control Scale. This quantitative design research used questionnaire method to obtain data. The data was analyzed using descriptive analysis, t - test Analysis and Correlation Statistic Analysis. Results showed an average level of Self-compassion and Self-control amongst recovering addicts. There were no significant differences in recovering addicts’ Self-compassion and Self-control mean score based on age, race, marital status, educational level and duration involved in drugs. Results also showed there was an inverse correlation between Self- compassion and Self-control (r = - 0.48, n = 190 , p < 0.001). The findings from this study provides useful understanding on the level of Self-compassion and Self-control amongst recovering addicts. Thus, both Self-compassion and Self-control could be given emphasis for future drug prevention and rehabilitation programs in Malaysia.